PELATIHAN PENGOLAHAN PRODUK BUAH MANGROVE UNTUK MENDUKUNG PENGEMBANGAN NUSA LEMBONGAN SEBAGAI DESTINASI WISATA - Arthana, I.W.; Restu, I.W.; Dewi, A.P. W. K.; Pratiwi, M.A.; Ekawaty, R.; Widiastuti, Widiastuti; Negara, K.W. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Nusa Lembongan is a tourism and maritime culture that has a fairly rapid tourism development. Nusa Penida coastal areas, especially in Nusa Lembongan and Nusa Ceningan there are 230.07 hectares of mangrove forest. Found 13 mangrove species and seven species of plant associations. Economically, the mangrove ecosystem to function as a productive fishing ground. In addition, mangrove also produces a variety of products such as wood, dyes, food, honey, medicines, cosmetics and others. The problem based on analysis of the situation that has been described is a community of Nusa Lembongan not know how to process the fruit of mangroves into several types of products that have economic value. This activity is carried out in three stages, namely: approach to the problem, training the fruit of mangroves processing and monitoring after training. The results showed that participants understand the material given during training activities. The success shown by the positive response from the participants when the training activities and the participants also did the development of the technique of making mangrove sticks after the training activity. Through this activity, participants are expected to utilize the fruit of mangrove as one of the charms in the development of tourism in Nusa Lembongan.